2016
DOI: 10.1097/mao.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

Serial cVEMP Testing is Sensitive to Disease Progression in Ménière Patients

Abstract: cVEMP is able to track progression in Ménière's disease over time. Thresholds were the most effective outcome measure to both track progression and to distinguish between MAV and Ménière's patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In particular, the correlation of VEMP amplitudes/AR with clinical symptoms and inner ear ELH deserves special attention. For MD, both the degree of ELH in the affected ear [45,46] and the AR of cVEMP amplitudes increase over time [32,41], which is in line with progressive permanent damage to the sensory epithelia of the labyrinth. Assuming that VM does not result in permanent hair cell damage or neuronal degeneration of the inner ear, we hypothesize that VEMP amplitudes/AR and the degree of ELH would fluctuate over time without progressive deterioration as observed for MD.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In particular, the correlation of VEMP amplitudes/AR with clinical symptoms and inner ear ELH deserves special attention. For MD, both the degree of ELH in the affected ear [45,46] and the AR of cVEMP amplitudes increase over time [32,41], which is in line with progressive permanent damage to the sensory epithelia of the labyrinth. Assuming that VM does not result in permanent hair cell damage or neuronal degeneration of the inner ear, we hypothesize that VEMP amplitudes/AR and the degree of ELH would fluctuate over time without progressive deterioration as observed for MD.…”
Section: Discussionmentioning
confidence: 86%
“…To the best of our knowledge, only one study has compared cVEMP recordings between patients with MD and VM at two different points in time. Van Tilburg and coworkers [41] observed an increase in cVEMP amplitude AR after a mean followup period of 2 years in MD patients, while no significant changes were observed in VM patients. Although the results of the present study are very preliminary due to the small sample size, they indicate variable degrees of asymmetry over time (in particular in patient VM 2 with a short disease history), in contrast to the steady increase in AR observed for the two MD patients (Figs.…”
Section: Monitoring Of Vemps In Single Patientsmentioning
confidence: 92%
“…In the current study, well-defined MD patients were compared with healthy controls to investigate how well cVEMP detects saccular dysfunction. Clinically, the ability to detect saccular dysfunction with cVEMPs could potentially be used to identify patients whose symptoms are suggestive, but not diagnostic for MD, as well as to track saccular function over time (38). It appears that different stages of MD may be accompanied by different cVEMP outcomes, with an increase in cVEMP thresholds for patients with more advanced disease (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cVEMP absence was highly correlated with hearing loss in the other study (43). Further, VEMPs were used to indicate control of vertigo caused by MD (44), and cVEMP was suggested to be implemented to track progression of MD (45). These studies suggested that the test results of vestibular functions might be helpful to identify the progress of MD.…”
Section: Discussionmentioning
confidence: 99%